Sharia Business Ethics Online Forex Trading at Company Signal Providers Volatility 75 Index JR (VIXJR) - Gresselda Sharen Firli (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2023)
This study aims to determine the practice and application of sharia business ethics in forex trading of JR Volatility 75 Index companies in the forex market and the dissemination of the results of the analysis and transactions to registered members. This research is qualitative research with the research object of corporate signal provider Volatility 75 Index JR. Data collection methods used are observation, in-depth interviews, and documentation. The results of the study show that JR's Volatility 75 Index has implemented sharia business ethics in its service business so as to make it feel safe and comfortable when using the forex market analysis services from the company.